As Áreas de riscos hidrológicos no município de Ourinhos/SP - Guerra, Franciele Caroline [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work aims to evaluate the vulnerable areas to hydrological risks, such as, flooding, inundation and overflowing in the city of Ourinhos (SP), with the purpose of assisting in the municipal public policies aiming at the sustainability and management of environmental urban patrimony. For that, it was used the concepts of vulnerability, hazard and environmental patrimony. In an etymological approach, the word hazard means a situation of danger, vulnerability can be understood as susceptibility by the human being in a situation of danger or damage, and environmental patrimony are all elements considered by the processes of cultural construction of urban environment - understood as materialization of social relations. When related to cartography, its objects become important indicators of sustainability in territorial ordering, because spatialize the areas of potential and vulnerabilities of a given territory, contributing directly to municipal public policy proposals that make up the steps of environmental planning. So, based on the new federal environmental policies − in particular Law Nº 12.608/2012 − which establish as competence of the municipalities identify and incorporate the mappings of risks and vulnerabilities, promoting supervisory of these areas for urban environmental patrimony preservation. The work adopts as theoretical conception the method of investigation of the systemic analysis of the landscape, in which nature, man, society and culture are now planned and understood in an integrated way. In order to do so, Alves (2006) considered the methodological approach to allow examples with relevant indicators and variables on the theme involved and the criteria for analysis and hazard classification of the Ministry of Cities...

Este trabalho tem como objetivo avaliar as áreas vulneráveis a riscos hidrológicos, por alagamentos, enchentes, enxurradas e inundações no município de Ourinhos (SP), com o intuito de auxiliar nas políticas públicas municipais visando a sustentabilidade e gestão do patrimônio ambiental urbano. Para isso, utilizou-se como base os conceitos vulnerabilidade, risco e patrimônio ambiental. Em uma abordagem etimológica, a palavra risco significa situação de perigo, vulnerabilidade pode ser entendida como suscetibilidade por parte do ser humano a uma situação de perigo ou dano, e patrimônio ambiental são todos os elementos considerados pelos processos de construção cultural do ambiente urbano - entendido enquanto materialização das relações sociais. Se relacionados à cartografia de síntese, seus objetos tornam-se importantes indicativos de sustentabilidade na ordenação territorial, pois espacializam as áreas de potencialidades e vulnerabilidades de um dado território, contribuindo diretamente para propostas de políticas públicas municipais que compõem as etapas de planejamento ambiental dos Planos Diretores. Assim, tomando como base as novas políticas ambientais federais − em especial a Lei nº 12.608/2012 −, que estabelecem como competência dos municípios identificar e incorporar os mapeamentos de riscos e vulnerabilidades, promovendo a fiscalização dessas áreas para a preservação do patrimônio ambiental urbano. O trabalho adota como concepção teórica o método de investigação da análise sistêmica da paisagem, em que natureza, homem, sociedade e cultura passam a ser planejados e compreendidos de maneira integrada. Para isso, utilizouse como metodológica as considerações de Alves (2006) por permitir exemplos dotados de indicadores e variáveis relevantes sobre a temática envolvida e os critérios de análise e de classificação de riscos do Ministério das Cidades...
Keywords: Cartografia; Sustentabilidade; Hidrologia